Potassium Fulvate Alleviates Salt–Alkali Stress and Promotes Comprehensive Growth of Oats in Saline–Alkali Soils of the Qaidam Basin - Xin Jin; Jie Wang; Xinyue Liu; Jianping Chang; Caixia Li; Guangxin Lu (Plants, 2025)
Soil salinization limits global agricultural sustainability, and extensive areas of saline–alkaline soils on the Qinghai–Tibet Plateau remain underutilized. Against this backdrop, this study evaluated the effects and ecological regulatory mechanisms of potassium fulvate (PF) application on oat (Avena sativa L.) growth, soil properties, and rhizosphere microbial communities in the saline–alkali soils of the Qaidam Basin. The results showed that PF significantly enhanced both aboveground and belowground biomass and improved root morphological traits, with the higher application rate (150 kg·hm−2) showing superior performance. PF also effectively improved soil nutrient conditions (organic matter, ammonium nitrogen, and potassium), reduced the integrated salinity–alkalinity index, significantly optimized the composition of rhizosphere soil cations (increased K+ and Ca2+; decreased Na+ and Mg2+), and induced a marked reshaping of the composition and structure of rhizosphere microbial communities. Notably, microbial β-diversity exhibited a significant regulatory effect on the comprehensive growth of oats. Structural equation modeling (SEM) revealed that PF primarily promoted oat growth indirectly by improving soil physicochemical properties (direct effect = 0.94), while the microbial community structure served as a synergistic ecological mediator. This study clarifies the regulatory mechanisms of PF in oat cultivation under alpine saline–alkali conditions, providing both theoretical and practical support for improving soil quality, enhancing forage productivity, and promoting sustainable agriculture in cold regions.